Strange exit - Peevyhouse, Parker (Tor Teen, 2020)
Seventeen-year-old Lake seeks the secret heart of the computer simulation that safeguards passengers aboard a ship orbiting a post-apocalyptic Earth, on a quest that will either save or destroy them all.